Influence of sub-band gap density of states on the electrical performance of amorphous SiZnSnO thin film transistor. (February 2022) - Saha, D.; Lee, Sang Yeol
Highlights: Fabrication of Indium and Gallium free naturally abundant and inexpensive materials based Si-Zn-Sn-O TFT. Sub-band gap DOS model of amorphous Si-Zn-Sn-O has been proposed. Gaussian shallow donor-like and deep level acceptor-like trap states are predicted in the DOS model. Disorder asymmetry is observed between conduction and valence band tail states of amorphous SiZnSnO. Conduction band tail states density is found to be much lower than that of amorphous Si:H. Abstract: Fabrication, electrical characterizations and numerical simulations are performed on radio-frequency sputtered amorphous SiZnSnO thin film transistors (TFTs). Experimental transfer curves are compared with numerically simulated results to extract the nature of sub-band gap density of states (DOS) of the amorphous channel materials. Defect states arising due to disorder induced localization of electronic wave functions is considered in the numerical simulation process. The extracted DOS for conduction band tail is found to be roughly two order of magnitude lower than that of the a-Si:H. Moreover, disorder asymmetry is also observed between conduction and valence band tail states. In addition to band tails, Gaussian shallow donor-like states and deep level acceptor-like traps are also taken into consideration. The influence of these defect states on the electrical performance of SiZnSnO TFTs has been investigated in detail. Such studies are useful for fundamental understanding of device physics and further improvement of amorphous SiZnSnO based TFT performance and stability.